Analysis of the Factors Influencing Willingness to Connect in Sistem Penyediaan Air Minum (Spam)/Drinking Water Supply System (Dwss) Pekanbaru Riau Using Binary Logistic Regression Method - Herry K, Raras; Mulyani, Sarah; Heikal, Jerry (Journal Research of Social Science, Economics, and Management, 2026)
To fulfill the needs for clean water in Pekanbaru City and Kampar Regency Riau, Perusahaan Daerah Air Minum(PDAM)/Drinking Water Regional Enterprise (DWRE) in collaboration with an investor company is building piping network infrastructure known as the Pekanbaru – Riau Sistem Penyediaan Air Minum (SPAM)/Drinking Water Supply System (DWSS). This SPAM/DWSS has an important role in fulfilling the needs for clean water in the community. However, its operational sustainability is highly dependent on the ability of potential customers to pay for the services (willingness to connect). This study aims to analyze factors influencing the willingness to connect for prospective customers of SPAM/DWSS Pekanbaru – Kampar by using the binary logistic regression method. The independent variables analyzed include economic, social, and demographic factors, such as age, occupation, household income, education level, and customer perception of water tariffs. The data were collected through a survey conducted by RH Consultants to 2,000 respondents of domestic customers and 1,500 respondents of commercial and industrial customers to determine the most significant factors influencing the willingness to connect. The results showed that household income has a significant influence on the willingness to connect for potential customers. These findings provide insights for SPAM/DWSS managers and local governments in designing more equitable and sustainable tariffs and policies.